Virus‐Mimicking Cell Membrane‐Coated Nanoparticles for Cytosolic Delivery of mRNA. (29th November 2021) - Park, Joon Ho; Mohapatra, Animesh; Zhou, Jiarong; Holay, Maya; Krishnan, Nishta; Gao, Weiwei; Fang, Ronnie H.; Zhang, Liangfang
Abstract: Effective endosomal escape after cellular uptake represents a major challenge in the field of nanodelivery, as the majority of drug payloads must localize to subcellular compartments other than the endosomes in order to exert activity. In nature, viruses can readily deliver their genetic material to the cytosol of host cells by triggering membrane fusion after endocytosis. For the influenza A virus, the hemagglutinin (HA) protein found on its surface fuses the viral envelope with the surrounding membrane at endosomal pH values. Biomimetic nanoparticles capable of endosomal escape were fabricated using a membrane coating derived from cells engineered to express HA on their surface. When evaluated in vitro, these virus‐mimicking nanoparticles were able to deliver an mRNA payload to the cytosolic compartment of target cells, resulting in the successful expression of the encoded protein. When the mRNA‐loaded nanoparticles were administered in vivo, protein expression levels were significantly increased in both local and systemic delivery scenarios. We therefore conclude that utilizing genetic engineering approaches to express viral fusion proteins on the surface of cell membrane‐coated nanoparticles is a viable strategy for modulating the intracellular localization of encapsulated cargoes. Abstract : Cell membrane‐coated nanoparticles are engineered to express a viral fusion protein, thus enabling them to exhibit improved endosomal escape properties. It is demonstrated that these virus‐ mimicking nanocarriers are able to deliver mRNA payloads to the cytosolic compartment after cellular uptake, enhancing expression of the encoded proteins both in vitro and in vivo.